Acaricidal Properties of Bio-Oil Derived From Slow Pyrolysis of Crambe abyssinica Fruit Against the Cattle Tick Rhipicephalus microplus (Acari: Ixodidae) - Mattos, Camila; Andrade, Juliana; Salarini Peixoto, Bruno; Tavares Moraes, Nayara Luiza; da Cunha Veloso, Marcia Cristina; Alves Romeiro, Gilberto; Folly, Evelize das Chagas (Frontiers in Physiology, 2021)
Slow pyrolysis is a process for thermochemical conversion of biomasses into bio-oils, which may be rich in diverse chemicals with biotechnological potential. Bio-oil from crambe fruits was obtained to investigate a potential acaricidal effect. Slow pyrolysis of crambe fruits was performed in a batch reactor at 400 ºC, and the chemical composition of the resulting material was analyzed by GC-MS. The bio-oil was tested in bioassays against larvae and engorged females of the cattle tick Rhipicephalus microplus, using Larval Packet Test (LPT) and Adult Immersion Test (AIT), respectively. GC-MS revealed that crambe fruit bio-oil was composed mainly of hydrocarbons such as alkanes and alkenes, phenols, and aldehydes. The bio-oil had an LC90 of 14.4% against tick larvae. In addition, crambe bio-oil caused a female mortality of 91.1% at a concentration of 15%, and a strong inhibition of oviposition. Ovaries from treated females were dissected for examination, and a significant reduction in gonadosomatic index was observed, indicating that bio-oil interfered in tick oogenesis. Altogether, these results suggest that slow pyrolysis of crambe fruit yields a sustainable and eco-friendly candidate product for the control of cattle tick R. microplus.